2013
DOI: 10.3341/kjo.2013.27.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 20-Gauge Conventional Vitrectomy Technique with the 23-Gauge Releasable Suture Vitrectomy Technique

Abstract: PurposeTo compare the efficacy of the transconjunctival releasable suture technique for pars plana vitrectomy using 23-gauge (23G) instruments versus the conventional 20-gauge (20G) technique.MethodsA retrospective and interventional case series was consecutively performed for 199 eyes of the 192 patients that were a part of this study. Clinical data were reviewed retrospectively regarding the operation time, preoperative and postoperative intraocular pressure, visual acuity and astigmatism for 54 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…They reported that the mean operation time was 88.5 ± 20.1 in the 23G vitrectomy group and 102.1 ± 23.1 minutes in the 20G conventional group, respectively ( p =0.01). 13 This result was similar to results reported in our study. The difference in the surgical duration was mainly because of opening and closing time required with 20G vitrectomy despite that 20G vitrectomy is quicker once we exclude the opening and closing time required before starting vitrectomy.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…They reported that the mean operation time was 88.5 ± 20.1 in the 23G vitrectomy group and 102.1 ± 23.1 minutes in the 20G conventional group, respectively ( p =0.01). 13 This result was similar to results reported in our study. The difference in the surgical duration was mainly because of opening and closing time required with 20G vitrectomy despite that 20G vitrectomy is quicker once we exclude the opening and closing time required before starting vitrectomy.…”
Section: Discussionsupporting
confidence: 93%
“…as compared to those requiring partial vitrectomy (macular hole, epiretinal membrane etc). This observation is comparable to another such study conducted recently by Kim et al 13 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As previous studies have shown, the 23G PPV system is less invasive than 20G PPV, and the incidence of early-onset ocular hypertension in patients treated with 23G PPV is lower than that in patients treated with 20G PPV. 2 , 3 Furthermore, macular disease presents a lower risk of elevated IOP after PPV than other vitreoretinal disorders. 25 , 26 Therefore, the reduced use of IOP-lowering drugs might be the result of more refined PPV instruments and procedures and the increase in the proportion of patients with macular diseases.…”
Section: Discussionmentioning
confidence: 99%